Perceived determinants and barriers of recruitment process outsourcing in service sector of Pakistan: a qualitative approach. (28th August 2021) - Memon, Mehreen; Aqil, Muhammad; Soomro, Kamran Ahmed; Adeel, Ahmad
This study aims at finding out the determinants for and barriers in recruitment process outsourcing. The study adopts qualitative approach and phenomenology has been used as research methodology. The study is based on in-depth interviews with HR professionals in ten organisations. The analysis is conducted through thematic analysis. The study finds out that diversified pool of candidates, bulk hiring, professional expertise, replacement option, focus on core HR responsibilities and promoting fair recruitment process are the major determinants for adopting RPO by organisations. The factors such as additional cost, RPO branding with non-management positions, incompatibility issues and emotional detachment are the major barriers in adopting RPO. The study suggests that the use of RPO in small size organisations as an emerging theme. Organisations can make decision of adopting RPO for management level positions according to the determinants highlighted in the study.